2020
DOI: 10.3390/molecules25132978
|View full text |Cite
|
Sign up to set email alerts
|

Stereodivergent Synthesis of Camphor-Derived Diamines and Their Application as Thiourea Organocatalysts

Abstract: A series of 18 regio- and stereo-chemically diverse chiral non-racemic 1,2-, 1,3-, and 1,4-diamines have been synthesized from commercial (1S)-(+)-ketopinic acid and (1S)-(+)-10-camphorsulfonic acid. The structures of the diamines are all based on the d-(+)-camphor scaffold and feature isomeric diversity in terms of regioisomeric attachment of the primary and the tertiary amine function and the exo/endo-isomerism. Diamines were transformed into the corresponding noncovalent bifunctional thiourea organo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Camphor-derived endo -diamines 1a , b and exo -diamines 2a were prepared in four steps from commercially available (1 S )-(+)-10-camphorsulfonic acid ( Scheme 1 ) [ 29 , 30 ]. Camphorsulfonic acid was transformed into 10-iodocamphor in an Apple-type reaction, followed by nucleophilic substitution with pyrrolidine or dimethylamine in dimethyl sulfoxide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Camphor-derived endo -diamines 1a , b and exo -diamines 2a were prepared in four steps from commercially available (1 S )-(+)-10-camphorsulfonic acid ( Scheme 1 ) [ 29 , 30 ]. Camphorsulfonic acid was transformed into 10-iodocamphor in an Apple-type reaction, followed by nucleophilic substitution with pyrrolidine or dimethylamine in dimethyl sulfoxide.…”
Section: Resultsmentioning
confidence: 99%
“…As part of our ongoing study of camphor-based diamines as potential organocatalyst scaffolds [ 29 ], we reported the synthesis of 1,3-diamine-based bifunctional squaramide organocatalysts prepared from camphor and their application as efficient catalysts in Michael additions of 1,3-dicarbonyl compounds and pyrrolones as nucleophiles to trans -β-nitrostyrene derivatives [ 30 , 31 ]. Extending this work, we report here the synthesis of a new type of 1,3-diamine-based bifunctional quaternary ammonium salt phase-transfer organocatalyst ( Figure 1 ) and its evaluation in the electrophilic α-functionalization of β-keto ester and the alkylation of a glycine-derived Schiff base with methyl acrylate.…”
Section: Introductionmentioning
confidence: 99%
“…Organocatalysts Ia [70], II [69], IIIa [70], IV [70], Vb [74], VIa [75], VIb [76], VIIa [77], VIIb [76], IXa [78], IXb [79], IXc [80], Xb [81], XIa [19], and XIb [78] were prepared following the literature procedures; organocatalysts VIIIb and XII were purchased from Sigma-Aldrich. To a solution of methyl (Z)-2-(2-chloroacetyl)-3-(methylamino)but-2-enoate (E) [71] (1 equivalent) in anhydrous EtOH at room temperature, KOH (1.05 equivalent, ω = 0.85) was added and the resulting reaction mixture was heated to 75 • C. After the disappearance of the starting material (ca.…”
Section: Materials and Methods Syntheses And Characterizationmentioning
confidence: 99%
“…(+)‐Camphoric acid was chosen as the precursor because it is an inexpensive source of chirality, readily available in both enantiomeric forms and has been used as a ligand on enantioselective metallic catalysis with good results 44 . Moreover, most of the organocatalysts synthesized in this report have the advantage of being easily prepared in a synthetic sequence of only two steps from (+)‐camphoric acid, differently from the 1,3‐diamine bifunctional organocatalysts reported in the literature 36–43 …”
Section: Introductionmentioning
confidence: 99%
“…Bifunctional 1,3‐diamine thiourea and squaramide organocatalysts derived from camphor were also used for the same transformations; however, these organocatalysts required five to nine synthetic steps (Figure 1). 40,41 Likewise, 1,3‐diamine‐tethered guanidium/bisthiourea organocatalysts have been used in Michael reactions between 1,3‐dicarbonyl compounds and nitroolefins 42 and in the enantioselective phospha‐Michael reaction of diphenyl phosphonate to nitroolefins (Figure 1). 43 …”
Section: Introductionmentioning
confidence: 99%